Kinetics of thermal oxidation of coals, industrial wastes, and their mixtures; Powder Technology; Vol. 454 - Dorokhov V. V. Vadim Valerjevich; Kuznetsov G. V. Geny Vladimirovich; Paushkina K. K. Kristina Konstantinovna; Strizhak P. A. Pavel Alexandrovich (2025, 2025)
Title screen